PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ARDHAYA BUMI PERSADA HALIM JAKARTA TIMUR - Thomas Angra Hanovan; Muhammad Harri; Farah Valensiyah Inggrid (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
The purpose to analyze the influence of work motivation and work environment on the performance employees of PT. Ardhaya Bumi Persada Halim, East Jakarta. This research is included in the category of causal associative research using a quantitative approach. The research population employees of PT. Ardhaya Bumi Persada Halim, East Jakarta,. The technique used for sampling is simple random sampling, sampling members from the population is carried out randomly without paying attention to the strata in the population. The analytical method uses simultaneous linear regression analysis. The results of the research show that work motivation and work environment have a positive and significant effect on the performance employees of PT. Ardhaya Bumi Persada Halim, East Jakarta